Persepsi Masyarakat terhadap Urgensi Akta Nikah - Tafria Wenny Wulandari; Fitri Eriyanti; Aldri Frinaldi (Journal of Education on Social Science (JESS), 2019)
This study aims to analyze people's perceptions of the urgency of a marriage certificate in Linggo Sari Baganti District, Pesisir Selatan Regency. This research method is Qualitative Descriptive, with several informants as data sources that are determined based on appropriate criteria through direct observation on the object of research and interviews. Secondary data that supports this research are obtained from the documents available at the object of research. To test the validity of the data used Triangulation Technique. Based on the information from the informants of this study, it can be explained that the public perception of the marriage certificate still considers the marriage certificate as not urgent and not important so that the administrative management is not completed because it considers it not urgent so the community neglects the marriage certificate. The community still perceives the management to be long and complicated, even though after the author compares the data in the field regarding the management procedures, it is not difficult to take care of it. Obstacles in the management of marriage certificates faced by the community are related to customary arrangements and the lack of file requirements submitted to KUA. Efforts made by KUA to deal with these obstacles are like conducting counseling to each village about the importance of marriage certificates. Based on the research above the recommendations that the writer can suggest to the community are expected to be willing to take part in socialization and counseling about marriage registration. So that people can know and understand the importance of marriage certificates. Responsible parties such as KUA, P3N and the government are expected to be able to increase socialization regularly.Keywords: Community Perception, Urgency, Marriage Deed.